Modeling and validation of a 7-dof full car for ride quality - Mohd. Samin, Pakharuddin (2007)
The validation was done by comparing the simulation results. A ride test was conducted at two different speeds, and the simulation results consist of roll angle, pitch angle, and vehicle body displacement are analyzed.